2016
DOI: 10.1016/j.jvolgeores.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Volcano–hydrothermal system of Ebeko volcano, Paramushir, Kuril Islands: Geochemistry and solute fluxes of magmatic chlorine and sulfur

Abstract: Ebeko volcano at the northern part of Paramushir Island in the Kuril island arc produces frequent phreatic eruptions and relatively strong fumarolic activity at the summit area~1000 m above sea level (asl). The fumaroles are characterized by low-temperature, HCl-and S-rich gas and numerous hyper-acid pools (pH b 1) without drains. At~550 m asl, in the Yurieva stream canyon, many hot (up to 87°C) springs discharge ultra-acidic (pH 1-2) SO 4 -Cl water into the stream and finally into the Sea of Okhotsk. During q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
0
18
0
6
Order By: Relevance
“…The postglacial cone of Ebeko is composed of lava flows and pyroclastics of andesitic composition. A short review of the phreatic activity of the volcano since that event can be found in Kalacheva et al (2016). The modern phreatic and fumarolic activity of Ebeko started after a strong explosive phreatic-magmatic eruption from the Middle crater in 1934-1935(Gorshkov, 1970Melekestsev et al, 1993).…”
Section: Sampling and Measurement Locationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The postglacial cone of Ebeko is composed of lava flows and pyroclastics of andesitic composition. A short review of the phreatic activity of the volcano since that event can be found in Kalacheva et al (2016). The modern phreatic and fumarolic activity of Ebeko started after a strong explosive phreatic-magmatic eruption from the Middle crater in 1934-1935(Gorshkov, 1970Melekestsev et al, 1993).…”
Section: Sampling and Measurement Locationsmentioning
confidence: 99%
“…4.1.5. Some of the data for Ebeko fumaroles are taken from other sources (Kalacheva et al, 2016;Menyailov et al, 1985). Some of the data for Ebeko fumaroles are taken from other sources (Kalacheva et al, 2016;Menyailov et al, 1985).…”
Section: Systematics Of the N 2 -Ar-he-ne Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent Multi-GAS compositional measurements in the plumes of hyperacidic crater lakes (de Moor et al, 2016;Gunawan et al, 2016;Shinohara et al, 2015;Tamburello et al, 2015) have shown that SO 2 escapes through lake-water surfaces during pH < 1 gas-water interactions. HCl, another acidic gas species generally considered reactive in aqueous solutions, was detected in emissions from hyperacid springs (e.g., Kalacheva et al, 2016). Recently, Capaccioni et al (2017) and Rodríguez et al (2017) experimentally demonstrated that HCl is increasingly released from a "lab-lake" when pH drops below À0.2.…”
Section: Introductionmentioning
confidence: 99%